Spin transitions in a series of [Fe(pybox)2]2+ complexes modulated by ligand structures, counter anions, and solvents. Issue 12 (11th November 2016) - Zhu, Yuan-Yuan; Li, Hong-Qing; Ding, Zhong-Yu; Lü, Xiao-Jin; Zhao, Liang; Meng, Yin-Shan; Liu, Tao; Gao, Song
Abstract : A new family of mononuclear Fe(ii ) compounds is synthesized based on pybox ligands. Their spin-crossover behaviours can be effectively mediated by ligand structures, counter anions, and solvents. Abstract : Herein, we investigate the spin transition properties in a series of mononuclear Fe(ii ) complexes constructed by two pybox ligands and four counter anions.1(BF4 ) undergoes an abrupt spin-transition at around 150 K, which proceeds to 50% completeness and is accompanied by a structural phase transition.1(BPh4 )·MeCN, 2(ClO4 ), and2(BF4 ) all display gradual and complete SCO behaviours around or above ambient temperature. The desolvated compound1(BPh4 ) exhibits a gradual but incomplete SCO.2(PF6 )·MeCN, 2(PF6 ) and2(BPh4 ) show a two-step SCO. The well-defined two-step SCO of2(BPh4 ) takes place at 100–200 K ( T 1/2 = 150 K) and 400–500 K ( T 1/2 = 446 K). In contrast, compounds1(BF4 )·MeCN, 1(PF6 )·MeCN·Et2 O and1(PF6 ) remain high-spin at the measured temperatures. The LIESST (light induced excited spin state trapping) effect of several SCO compounds are also investigated, which display photo-conversion during light irradiation at low temperature at a relatively high level. Our results demonstrate that the [Fe(pybox)2 ] 2+ series of complexes will become a new versatile system in spin-crossover research.